Consumer Purchasing Decisions in Review of Viral Mareting, Brand Ambassador and Brand Image on Skincare Products in Sidoarjo - Syahputri, Denisa Firlian; Sari, Dewi Komala; Oetarjo, Mas (Universitas Negeri Padang, 2024)
This study aims to determine the effect of viral marketing, brand ambassadors, and brand image on purchasing decisions on skincare products in Sidoarjo. This research uses a quantitative approach with the population is people in Sidoarjo who have bought Avoskin products and are ≥17 years old. The sampling technique of this research was carried out by non-probability sampling method with purposive sampling technique with a total of 100 respondents. Collection techniques by distributing questionnaires and answers will be measured using a Likert scale. The data analysis technique in this study uses the PLS-SEM method with the help of SmartPLS 3.0 software. The results of this study prove that viral marketing affects purchasing decisions on Avoskin skincare products in Sidoarjo, brand ambassadors affect purchasing decisions on Avoskin skincare products in Sidoarjo, and brand image affects purchasing decisions on Avoskin skincare products in Sidoarjo.Keywords: Viral Marketing; Brand Ambassador, Brand Image; Purchasing Decisions; Avoskin